Metabotropic glutamate receptor genetic variants and peripheral receptor expression affects trait scores of autistic probands - Nilanjana Dutta; Mahasweta Chatterjee; Sharmistha Saha; Swagata Sinha; Kanchan Mukhopadhyay (Scientific Reports, 2024)
Abstract Glutamate (Glu) is important for memory and learning. Hence, Glu imbalance is speculated to affect autism spectrum disorder (ASD) pathophysiology. The action of Glu is mediated through receptors and we analyzed four metabotropic Glu receptors (mGluR/GRM) in Indo-Caucasoid families with ASD probands and controls. The trait scores of the ASD probands were assessed using the Childhood Autism Rating Scale2-ST. Peripheral blood was collected, genomic DNA isolated, and GRM5 rs905646, GRM6 rs762724 & rs2067011, and GRM7 rs3792452 were analyzed by PCR/RFLP or Taqman assay. Expression of mGluRs was measured in the peripheral blood by qPCR. Significantly higher frequencies of rs2067011 ‘A’ allele/ AA’ genotype were detected in the probands. rs905646 ‘A ‘exhibited significantly higher parental transmission. Genetic variants showed independent as well as interactive effects in the probands. Receptor expression was down-regulated in the probands, especially in the presence of rs905646 ‘AA’, rs762724 ‘TT’, rs2067011 ‘GG’, and rs3792452 ‘CC’. Trait scores were higher in the presence of rs762724 ‘T’ and rs2067011 ‘G’. Therefore, in the presence of risk genetic variants, down-regulated mGluR expression may increase autistic trait scores. Since our investigation was confined to the peripheral system, in-depth exploration involving peripheral as well as central nervous systems may validate our observation.